The Predictive Value of Growth Differentiation Factor-15 in Recurrence of Atrial Fibrillation after Catheter Ablation - Ying Wei; Shuwang Liu; Haiyi Yu; Yuan Zhang; Wei Gao; Ming Cui; Lei Li (Mediators of Inflammation)
The mechanisms underlying the recurrence of atrial fibrillation (AF) after radiofrequency catheter ablation (RFCA) are not well concerned. The study sought to explore the association between growth differentiation factor-15 (GDF-15) and the incidence of recurrent events among AF patients after the ablation procedure. We prospectively included 150 consecutive AF patients who underwent RFCA. Clinical information about the patients was collected. Blood samples on the second morning of hospital admission and three months after RFCA were collected, and enzyme-linked immunosorbent assay (ELISA) was used to measure the concentration of GDF-15. All participants were followed up at specific times (1st/3rd/6th/12th/18th/24th months) after RFCA to record recurrences events. During a median follow-up of 14.0 months, AF recurrence occurred in 37(24.7%) patients. Baseline serum GDF-15 level in the persistent AF group was significantly higher than the paroxysmal AF group [1140(854~1701)ng/L vs. 1062(651~1374)ng/L, P=0.039]. Baseline serum GDF-15 level in the recurrence group was significantly higher than the nonrecurrence group [1287(889~1768) ng/L vs. 1062(694~1373)ng/L, P=0.022]. Serum GDF-15 level at three months after RFCA was significantly lower than the baseline [870 (579~1270) ng/L vs. 1155 (735~1632)ng/L, P<0.001]. The baseline GDF-15 correlated significantly with LAP (r=0.296, P<0.001) and LAAV(r=−0.235, P=0.003). Kaplan-Meier analysis showed a significantly lower event-free survival time in the high baseline GDF-15 (≥1287.3 ng/L) group than the low baseline GDF-15 (<1287.3 ng/L) group (17.1 months vs. 20.4 months, Log Rank P=0.017). In the multivariate Cox regression, baseline GDF-15(HR 1.053, 95% CI 1.007-1.100, P=0.022) and LAD (HR 1.124, 95% CI 1.011-1.250, P=0.030) were independent predictors of AF recurrence after RFCA. Our study indicated increased preprocedural GDF-15 is associated with left atrial remodeling and acts as a predictor of AF recurrence after ablation.